p-Pompeiu-Hausdorff Metric on Space of Subsets Induced by Partial Metric - Ekayanti, Arta; Marjono; Muslikh, Mohamad; Fitri, Sa’adatul (Indonesian Journal of Mathematics and Applications, 2025)
In this paper, we give some properties of the p-Pompeiu-Hausdorff metric on the space of subsets induced by a partial metric. These results provide a generalization of Barich’s (2011) results in the setting of partial metric. The properties provided in this study complement those presented by Aydi et al (2012).